Pheochromocytoma Presenting with Upper GI Symptoms: A Case Report - Mougheesa Baig, Sidra Waseem Khan, Zara Shakeel, Afaq Ahmad, Khalid Javeed Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Pheochromocytomas are rare tumours originating in chromaffin cells, representing 0.1–1% of all secondary hypertension cases.1 A case of pheochromocytoma in a 34 year old male presenting with unusual symptoms of abdominal discomfort and vomiting is presented. He has been generally well in the past but started feeling excessively tired for last 4 years and had dyspepsia off and on. On presentation his blood pressure was 240/120 mmHg, and heart rate was 130bpm. There was no neurological deficit and rest of the physical examination was normal. Fundoscopic examination revealed copper wiring and AV nipping but no hemorrhages or papilledema.The aim of this case report is to emphasize the importance of secondary causes of hypertension and to keep in mind the unusual presenting symptoms of pheochromocytoma. Keywords: Gastrointestinal Disorders, Pheochromocytoma, Tumors